Medical device reprocessing: a regulatory model proposal for Brazilian hospitals - Costa, Eliana Auxiliadora Magalhães; Costa, Ediná Alves; Graziano, Kazuko Uchikawa; Padoveze, Maria Clara (Revista da Escola de Enfermagem da USP, 2011)
Medical device reprocessing is extremely important and complex, thus requiring both the operational skills for its implementation and the technical qualification of the professionals involved in the activity. The typical issues of medical device reprocessing involve technical, economical and regulatory aspects when involving either the so-called reusable articles or those considered as for a single use. The objective of the present study is to propose a new regulatory model for medical device reprocessing in Brazil that would, on the one hand, satisfy the requirements for quality and safety, as recommended in the literature and, on the other hand, prove to be operational under the conditions prevailing in Brazilian hospitals. The elaboration of the present normative proposal was based on the Consensus Conference technique among specialists in the area. Guided by the contribution of these specialists, a proposal is put forth of a regulatory model for reprocessing medical products, so as to address some previously identified gaps in the normative body currently used in Brazil.